Removal of Pb from sewage sludge by electrokinetics: Effect of pH and washing solution type - Hanay, Oezge; Hasar, Halil; Kocer, Nilufer Nacar; Ozdemir, Ozgur (Taylor & Francis Ltd, 2009)
In this study, the effect of pH and washing solution on the removal of lead from sewage sludge by electrokinetics was investigated. The six experimental runs were carried out at two different pH values - 3 and 4 - using acetic acid, nitric acid and phosphoric acid. In addition, the sequential chemical extraction scheme according to the BCR's (Community Bureau of Reference) guidelines was applied to the sludge samples to evaluate the effect of acidic solutions on Pb fractionation during electrokinetic processes. Using nitric acid as the washing solution resulted in the highest removal efficiency of Pb (39%) amongst all the experiments. Acetic acid also provided similar removal percentages (37% and 38%) at different pre-acidification conditions. On the other hand, the removal efficiencies were 36% and 27% with pre-acidification using phosphoric acid at pH 3 and 4, respectively, resulting in the lowest efficiencies. The results obtained by BCR analysis showed that the metal present near the anode partitioned in to more mobile forms while the metal near the cathode partitioned in to less mobile forms, such as precipitated or adsorbed forms, as the electrokinetic process proceeded. The inter-fractional transformations of Pb formed only when using acetic acid. The similar percentages obtained by using different washing solutions indicated that the type of acid used as washing solution was less effective than the values of pH for removal of Pb from sewage sludge during the electrokinetic process.
Keywords: electrokinetics; sewage sludge; lead; pre-acidification